(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: Premessa - 1. La Chiesa Ortodossa Macedone - 2. Problemi giuridici della costituzione della Chiesa Ortodossa (autocefala) di Ohrid - 3. Gli effetti dell’autocefalia e il consolidamento dello Stato della Macedonia del Nord - 4. L’ortodossia tra autocefalia e pluralismo confessionale - 5. L’ecumene ortodossa e la problematica gestione della diaspora - 6. Il ruolo dei Patriarcati della diaspora nel rinnovamento dell’Ortodossia. Orthodox autocephaly and confessional pluralism in Northern Macedonia ABSTRACT: The paper reconstructs the history of the Macedonian Orthodox Church and the path that led it, after many vicissitudes, to obtain autocephaly from the Serbian Orthodox Church, with the name of the Orthodox Church of Ohrid, using the mediation of the Ecumenical Patriarchate. The implications of the affair are analyzed with the schism that opposes the Ecumenical Patriarchate to the Russian Patriarchate and its repercussions on pan-Orthodox relations, also in relation to the Orthodox diaspora.